Pengaruh Kegunaan Media Pembelajaran Berbasis Inklusivitas terhadap Persepsi Pengguna: Studi dengan Sistem Skala Kegunaan (SUS) - Gusmarleni Gusmarleni; Ai Sutini; Dede Trie Kurniawan (PAKAR Pendidikan, 2024)
This study examines the perceived usability and its influence on user attitudes toward an inclusive learning media developed using Canva, deep learning, and Heyzine flipbook applications. Employing a quantitative approach with surveys and the System Usability Scale, data were collected from teachers and students in inclusive elementary schools. The results indicate high usability scores, perceived usefulness, and engagement levels, demonstrating the effectiveness of the media in supporting inclusive education practices. These findings align with existing theories on technology acceptance, emphasizing the importance of user-centered design in educational innovation. The research highlights the potential of integrating interactive multimedia tools to enhance learning experiences for diverse learners. It underscores the need for ongoing development informed by user feedback to ensure long-term adoption. This contribution offers practical insights for educators and developers aiming to create accessible and engaging digital learning environments. Overall, the study reinforces the critical role of usability in fostering positive perceptions and active participation in inclusive education settings.